SCREENING OF STAPHYLOCOCCUS AUREUS AND COAGULASE NEGATIVE STAPHYLOCOCCUS (CONS) FROM URINE SAMPLES. - Metri Basavaraj C; P, Jyothi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objectives: The resistance profile of isolated Gram-positive organisms such as Staphylococcus aureus were left undone despite the increasing prevalent rate of this organism in urinary tract infections (UTI) and its role in antibiotic resistance. Therefore, the current study was carried out to identify the antibiotic resistance pattern of the S. aureus and coagulase negative Staphylococcus (CONS). Methods: The study was carried out in the Department of Microbiology, Shri BM Patil Medical College, Bijapur, India over a period of 3 years from January 2010 to December 2012. Urine specimens from both outpatients and inpatients of our hospital having one or more urinary symptoms, such as burning during micturition, fever, pyuria, frequency of urine, dysuria, hematuria, flank pain, suprapubic discomfort, etc., were processed. Results: Out of total staphylococcal isolates, 55% were S. aureus and 45% were CONS. Out of total isolates of Staphylococci 60.5% were from inpatient department and 39.5% were from out patient department. Linezolid (9.52%) pepercillin/tazobactam (14.3%) cefoperazone/salbactan (28.6%) showed least resistance against S. aureus and penicillin-G (90.5%), cloxacillin (71.4%), ciprofloxacin (71.4%) showed highest resistance against S. aureus. CONS isolates showed similar resistance profile, but when compared with S. aureus, CONS were more sensitive to the all antibiotic used. Conclusion: This study observed that Staphylococcus is the one of the most common etiologic agent of UTI in our hospital. The drug of choice that could be considered in the treatment of UTI caused by staphylococcus in our setting are linezolid, pepercillin/tazobactam, cefoperazone/salbactan. Staphylococcus was found to be highly resistant to penicillin-G, cloxacillin, and ciprofloxacin. Keywords: Antimicrobial resistance, Drug resistance, Staphylococcus aureus, Coagulase negative staphylococcus, Urinary tract infections.